FAKTOR PENYEBAB PEMBENGKAKAN BIAYA YANG BERPENGARUH TERHADAP BIAYA AKHIR PADA PROYEK KONSTRUKSI GEDUNG - Meassa Monikha Sari; Tb. Sofwan Hadi; Aldiansyah (Jurnal Infrastruktur, 2020)
During the implementation of project construction, there were frequently problems arising come from many kind of factors. Therefore implementation of project construction is not only delay but also apprear a huge loss or a cost overrun. The research aims to identify which factors are the cause of the cost overrun that affects the final cost of the construction project, as well as to determine how the relationship and influence of the factor affects the final cost. The data collected in this research is by spreading the questionnaire to the labors in 4 building construction projects in Tangerang, Banten. Data processing is done using SPSS 23 program. Based on the results of the data processin, here is the order of factors that cause cost overrun: a. Bad weather that affects the decline in worker productivity; b. the available project drawing information is inadequate/incomplete hence there were many jobs should be repeated due to defects/false (poor quality); c. the job delays frequently and there were earthquakes, landslides and forest fires have been temporarily suspended; d. the job scope information is incomplete; e. the imprecision of estimation and often changes in scope of work/implementation. There is a very strong relationship between the factors causing the cost overrun to the final cost with a pearson correlation value 0.813 and a substantial influence of 65.3% of the cost overrun factors of the project's final cost.